The international experience of assessing the effectiveness of event - Сокира, Т. (Journal of Economic Research & Business Administration, 2017)
In the last decade, there have been significant changes in the choice of marketing communications technologies by Kazakhstani companies. Increasingly, in the marketing plans of enterprises and organizations, there is such a technology of promotion as event marketing. There is an increase in both event agencies specializing in event marketing, and the growth of consumers who have a high share of the budget for the use of this technology. At the same time, despite the popularity of this method of promotion, the issue of assessing the effectiveness of the proposed event by various event enterprises remains open, which is the reason for the latter, is unreasonable additional profit. Event-business has turned into a profitable and profitable business. As a result, the price of products and services of enterprises and organizations that use event-services has a tendency to unreasonably increase its value. Drawing on existing research conducted by foreign and domestic theorists and practitioners, an attempt is made to review, analyze and summarize various practices, methods and approaches to assessing the effectiveness of event marketing. The conducted research led to the conclusion that the establishment of more transparent and clear criteria in the evaluation of efficiency is the basis for companies in the search for ways to reduce the cost of marketing activities, to create a less expensive portfolio of integrated marketing communications.